"Bath salts" intoxication: a new recreational drug that presents with a familiar toxidrome. Issue 2 (4th March 2015) - Hall, Christine; Heyd, Christopher; Butler, Chris; Yarema, Mark
ABSTRACT: It is important for emergency physicians to be aware of new psychoactive agents being used as recreational drugs. "Bath salts, " which include 3, 4-methylenedioxypyrovalerone (MDPV), mephedrone, and methylone, are the newest recreational stimulants to appear in Canada. There are currently more than 12 synthetic cathinones marketed as bath salts and used with increasing frequency recreationally. Although these drugs are now illegal in Canada, they are widely available online. We present a case report and discuss bath salts intoxication and its anticipated sympathomimetic toxidrome, treatment strategies, and toxicologic analysis, Treatment should not rely on laboratory confirmation. Since the laboratory identification of such drugs varies by institution and toxicologic assay, physicians should not misconstrue a negative toxicology screen as evidence of no exposure to synthetic cathinones. Illicit bath salts represent an increasing public health concern that involves risk to the user, prehospital personnel, and health care providers.